13.2k views
2 votes
Pls help picture provided

Pls help picture provided-example-1
User Kakurala
by
5.6k points

2 Answers

1 vote

Answer:


33

Explanation:

The given quadratic equation is


1=2x^2+5x

We want to rewrite this equation in the form;


ax^2+bx+c=0

We add
-1 to both sides of the equation to obtain;


0=2x^2+5x-1

This is the same as


2x^2+5x-1=0

This implies that;


a=2,b=5,c=-1

We substitute these values into the expression
b^2-4ac


\Rightarrow 5^(2)-4(2)(-1)


=25+8


=33

User JohnTube
by
5.5k points
5 votes

Answer: second option

Explanation:

The standard form of a quadratic equation is:


ax^2+bx+c=0

Then, to write the quadratic equation given in the problem in standard form, you must substract 1 from both sides of the equation. Then you have:


2x^2+5x-1=0

Given the quadratic equation above, to find the value of
b^2-4ac you must substitute:

a=2; b=5 and c=-1 into
b^2-4ac

Thenrefore, you obtain the following result:


5^2-4(2)(-1)=33

User Denis Barushev
by
5.3k points